2021
DOI: 10.1002/met.2034
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of significant stratospheric ozone reductions over southern Brazil: A proposal for a diagnostic index for southern South America

Abstract: During the southern spring, a break of the polar vortex over the Antarctic continent frequently occurs. This results in the advection of ozone‐poor air mass (O3) to mid‐latitudes, characterizing the secondary effect of the Antarctic ozone hole (SEAOH). We present some distinct characteristics the eight greatest reductions of the total O3 column (TOC) over the central region of Rio Grande do Sul (RS, 29.5°S, 54°W), southern Brazil, between August and November from 2012 to 2016 and develop a full scalar diagnost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…This result was due to the mid-latitudes in the tropical stratosphere air masses displacement onto the ozone lamina, and the DYBAL code was used to identify the dynamic barriers positioning in the MIMOSA model. This has been encouraging new studies that aim to simulate and predict these events [68], using deep learning [90] and a new dataset, ERA-5 reanalysis [91], to investigate the long-term atmospheric dynamics behavior [92]. In October 2015, these events led to a +16.6 ± 54.6% UVI increase, even with a predominance of partly cloudy days [93].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was due to the mid-latitudes in the tropical stratosphere air masses displacement onto the ozone lamina, and the DYBAL code was used to identify the dynamic barriers positioning in the MIMOSA model. This has been encouraging new studies that aim to simulate and predict these events [68], using deep learning [90] and a new dataset, ERA-5 reanalysis [91], to investigate the long-term atmospheric dynamics behavior [92]. In October 2015, these events led to a +16.6 ± 54.6% UVI increase, even with a predominance of partly cloudy days [93].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the authors of [67], between 1979 and 2013, also observed 62 events of this type. As an initiative to predict this event's occurrence, the authors of [68] calculated O3 indices that showed great dexterity in representing these events, indicating the polar trough that advanced on southern Brazil with the largest negative O3 anomalies.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, [68], between 1979 and 2013, also observed 62 events these type. As an initiative to predict this events occurrence, [69] calculated O3 indices that showed great dexterity in representing these events, indicating the polar trough that advanced on Southern Brazil with the largest negative O3 anomalies.…”
Section: Introductionmentioning
confidence: 99%